The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsami.1c24131
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Releasing Tryptophan-Based Poly(ester urea)s Electrospun Composite Nanofiber Mats with Antibacterial and Antibiofilm Activities for Infected Wound Healing

Abstract: Bacterial biofilms on wounds can lead to ongoing inflammation and delayed reepithelialization, which brings a heavy burden to the medical systems. Nitric oxide based treatment has attracted attention because it is a promising strategy to eliminate biofilms and heal infected wounds. Herein, a series of tryptophan-based poly­(ester urea)­s with good biodegradation and biocompatibility were developed for the preparation of composite mats by electrospinning. Furthermore, the mats were grafted with a nitric oxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…During the electrospinning process, several jets are continuously elongated towards the collector, the solvent of the polymeric jets is evaporated quickly, phase separation occurs, the jet solidifies, and nanofibers are formed [ 9 ]. More importantly, the electrospun nanofibers exhibit decreased fiber diameter when compared with the microfibers fabricated from some conventional spinning methods, such as melt spinning, wet spinning, dry spinning, and dry-wet spinning, thus resulting in notably increased specific surface area, which is highly needed in several medicinal applications [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the electrospinning process, several jets are continuously elongated towards the collector, the solvent of the polymeric jets is evaporated quickly, phase separation occurs, the jet solidifies, and nanofibers are formed [ 9 ]. More importantly, the electrospun nanofibers exhibit decreased fiber diameter when compared with the microfibers fabricated from some conventional spinning methods, such as melt spinning, wet spinning, dry spinning, and dry-wet spinning, thus resulting in notably increased specific surface area, which is highly needed in several medicinal applications [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin supply antibacterial property at osteogenic potential of magnesium-doped calcium silicate [ 49 ], important to avoid antibiotic administration and for successful bone regeneration. Nanofiber with nitric oxide-based treatment promotes wound healing by improve collagen deposition, cells growth and regulate inflammatory factors [ 50 ], while electrospun radially-oriented nanofiber mats together with herbal compound loaded hydrogel accelerated in full-thickness skin wound healing in diabetic disease [ 51 ]. Thus, in this prospective study, our research could be considered a preliminary proof of concept whose findings indicated the formation of a highly stable system with promising features for health applications.…”
Section: Resultsmentioning
confidence: 99%
“…The electrospinning technique is one advanced method that allows the creation of microfibrous scaffolds with desired properties from various materials for use in tissue engineering, treatment of infected wounds, etc. [ 51 , 52 ], and it may be used for the controlled formation of multilayered scaffolds.…”
Section: Introductionmentioning
confidence: 99%